Dextrose modified bilosomes for peroral delivery: improved therapeutic potential and stability of silymarin in diethylnitrosamine-induced hepatic carcinoma in rats. (3rd July 2019) - Parashar, Poonam; Rana, Preeti; Dwivedi, Monika; Saraf, Shubhini A
Abstract: Hepatic carcinoma (HC) is one of the most prevalent cancers, ranked as the second most common cause of cancer-related deaths worldwide. Silymarin (SYL) has been reported for its anticarcinogenic activity against various types of cancer such as prostate, breast, ovary, colon, lung, bladder and liver. Due to poor solubility and low bioavailability SYL lacks satisfactory therapeutic value thus designing a suitable and effective delivery system of SYL can led to improved therapeutic potential. The present study was aimed to develop SYL-loaded dextrose (DEX) modified bilosomes for targeted delivery to HC cells. The DEX-modified bilosomes were prepared through thin-film hydration method and optimized employing Box Behnken design. The bilosomes were evaluated for percent entrapment, drug loading, in vitro release and cytotoxicity on Hep-G2 cells. The optimized DEX-SYL-BL exhibited a particle size of 219.3 ± 2.99 nm, percent entrapment of 62.32 ± 4.23%, drug loading of 34.56 ± 1.23% and 84.96 ± 2.76% drug release respectively over a period of 24 hr. The stability of bilosomes was ascertained in simulated gastric and intestinal fluids. Cytotoxicity studies revealed greater performance of DEX-SYL-BL in terms of reduced viability in Hep-G2 cell lines when compared with pure SYL and SYL-BL. Further DEX-modified bilosomes were evaluated in vivo for their therapeutic efficacy in DEN-induced (Diethylnitrosamine) hepatic carcinoma in animal model. The DEX-SYL-BL displayed higher therapeutic potential as revealed from enhanced survival and reduced tumour burden in animals. DEX-SYL-BL also displayed significant restoration of altered oxidative markers and SGOT, SGPT levels towards normal value when compared with pure SYL.